Soluble Urokinase Plasminogen Activator Receptor (suPAR) Independently Predicts Severity and Length of Hospitalisation in Patients With COVID-19 - Enocsson, Helena; Idoff, Cornelia; Gustafsson, Annette; Govender, Melissa; Hopkins, Francis; Larsson, Marie; Nilsdotter-Augustinsson, Åsa; Sjöwall, Johanna (Frontiers in Medicine, 2021)
Background: Efficient healthcare based on prognostic variables in hospitalised patients with COVID-19 could reduce the risk of complications and death. Recently, soluble urokinase Plasminogen Activator Receptor (suPAR) was shown to predict respiratory failure, kidney injury, and clinical outcome in patients with SARS-CoV-2 infection. The aim of this study was to investigate the value of suPAR as a prognostic tool, in comparison with other variables, regarding disease severity and length of hospital stay in patients with COVID-19. Patients and methods: Individuals hospitalised with COVID-19 (40 males, 20 females; median age 57.5 years) with a median symptom duration of 10 days and matched, healthy controls (n=30) were included. Admission levels of suPAR were measured in serum by enzyme-linked immunosorbent assay. Blood cell counts, C-reactive protein (CRP) levels, lactate dehydrogenase (LDH), plasma creatinine and estimated glomerular filtration rates were analysed and oxygen demand, level of care and length of hospitalisation recorded. Results: Patients had significantly higher suPAR levels compared to controls (P<0.001). Levels were higher in severely/critically (median 6.6 ng/mL) compared with moderately ill patients (median 5.0 ng/mL; P=0.002). In addition, suPAR levels correlated with length of hospitalisation (rho=0.35; P=0.006). Besides suPAR, LDH, CRP, neutrophil count, neutrophil-to-monocyte and neutrophil-to-lymphocyte ratio, body mass index and chronic renal failure were discriminators of COVID-19 severity and/or predictors of length of hospitalisation. Conclusion: Admission levels of suPAR were higher in patients who developed severe/critical COVID-19 and associated with length of hospital stay. In addition, we showed that suPAR functioned as an independent predictor of COVID-19 disease severity.